TEACHING VOCABULARY USING FLASHCARDS IN EFL CLASSROOM IN INDONESIA AND MALAYSIA - Saputri, Nada Ayu; Prasetyarini, Aryati (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2024)
The aim of this research is to investigate the effectiveness of Flash Cards as a learning medium in enhancing English language acquisition among students in a Guidance Centre in Malaysia and an elementary school in Waru. The participants included 8 students from a Malaysian Guidance Studio and 41 students from an elementary school in Waru, spanning grades 4 through 6. The use of Flash Cards proved to be beneficial for both teachers and students in teaching and comprehending English vocabulary, fostering a more interactive learning environment. Data for the research were collected through student perception tables and interviews. The findings suggest that incorporating flashcards into the learning process is an effective strategy for improving students' English vocabulary. The study anticipates that this approach will lead to increased student engagement and activity in English learning, providing them with more opportunities to practice vocabulary and sentence structures within real-life contexts. By utilizing Flash Cards, students are expected to engage more actively in practicing various vocabulary and sentence structures, enhancing their English language skills. This research encourages teachers to integrate this medium into their classrooms, making lessons enjoyable, comprehensible, and innovative in bolstering students' vocabulary.